Nomogram for predicting the unfavourable outcomes of percutaneous endoscopic transforaminal discectomy for lumbar disc herniation: a retrospective study - Jiang, Xiaofeng; Gu, Lili; Xu, Gang; Cao, Xuezhong; Jiang, Jian; Zhang, Daying; Xu, Mu; Yan, Yi (Frontiers in Surgery, 2023)
Objective To investigate and integrate multiple independent risk factors to establish a nomogram for predicting the unfavourable outcomes of percutaneous endoscopic transforaminal discectomy (PETD) for lumbar disc herniation (LDH). Methods From January 2018 to December 2019, a total of 425 patients with LDH undergoing PETD were included in this retrospective study. All patients were divided into the development and validation cohort at a ratio of 4:1. Univariate and multivariate logistic regression analyses were used to investigate the independent risk factors associated with the clinical outcomes of PETD for LDH in the development cohort, and a prediction model (nomogram) was established to predict the unfavourable outcomes of PETD for LDH. In the validation cohort, the nomogram was validated by the concordance index (C-index), calibration curve, and decision curve analysis (DCA). Results 29 of 340 patients showed unfavourable outcomes in the development cohort, and 7 of 85 patients showed unfavourable outcomes in the validation cohort. Body mass index (BMI), course of disease (COD), protrusion calcification (PC), and preoperative lumbar epidural steroid injection (LI) were independent risk factors associated with the unfavourable outcomes of PETD for LDH and were identified as predictors for the nomogram. The nomogram was validated by the validation cohort and showed high consistency (C-index = 0.674), good calibration and high clinical value. Conclusions The nomogram based on patients' preoperative clinical characteristics, including BMI, COD, LI and PC, can be used to accurately predict the unfavourable outcomes of PETD for LDH.